Is breastfeeding duration associated with caries in stunted toddlers? a cross-sectional study - Hidayah, Riski Amalia; Rochmawati, Mutia; Kinasih, Amelia Sekar (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Stunting remains a significant nutritional concern in Indonesia, potentially affecting physical and cognitive development. Stunting may lead to oral health issues, specifically dental caries, due to salivary gland atrophy in malnourished children. While dental caries have multiple contributing factors, breast milk contains protective proteins and antibacterial properties that may influence caries development. This study aims to investigate the association between breastfeeding duration and dental caries occurrence in stunted and non-stunted toddlers. An analytical observational study with a cross-sectional approach was conducted using quota sampling of 30 toddlers attending Sumingkir Village Posyandu. Spearman correlation analysis showed no significant correlation between breastfeeding duration and caries in both stunted (p = 0.68) and non-stunted groups (p =0.66). Independent T-test revealed no significant mean differences between the groups (p < 0.05). However, the Mann-Whitney test demonstrated a significant median difference in caries (p = 0.006) between stunting (4(0-6)) and non-stunting groups (0(0-18)). This study concludes that breastfeeding duration showed no correlation with caries in either stunted or non-stunted toddlers; however, nutritional status (stunting) appeared to influence caries occurrence in toddlers.